Morphological, structural and Physico-chemical properties of starch extracted from Banana pseudo stem: A Novel Starch (International Journal of Food and Nutritional Sciences, 2022)
The objective of the current study is to separate the starch from banana pseudostem of kokan local variety Velachi and characterize the isolated starch in order to investigate their functional qualities, granule morphology, crystalline pattern, amylose content and physical as well as chemical compositions. For characterization, a variety of methods were employed, including scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FT-IR). The amylose concentration of the banana pseudo-stem starch was determined to be 11.94 g/100g. According to SEM measurements, banana pseudo-stem starch had smooth surfaces and uniform, elongated, circular ridges between 15 to 65 µm in length. According to the data gathered from this study, the kokan local banana pseudo-stem isolated starch has a variety of applications, particularly in the food, drug, and cosmetics industries where they can be utilized as thickeners, edible coatings, fat substitutes, and other similar applications. Additionally, functional foods containing banana starch may be suggested for those with diabetes